2017
DOI: 10.1016/j.aogh.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Marriage Timing on Women's and Children's Health in Sub-Saharan Africa and Southwest Asia

Abstract: Background. Age of marriage is a barrier to mother's health care around pregnancy and children health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 22 publications
1
33
1
4
Order By: Relevance
“…Adolescent or young mothers experience a greater lack of access to essential maternal and child health services (Delprato & Akyeampong, 2017) and have lower decision-making autonomy than older mothers (Kamiya et al, 2018). Importantly, the adverse effects of these disadvantages on child nutritional status would be greater when children are younger.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent or young mothers experience a greater lack of access to essential maternal and child health services (Delprato & Akyeampong, 2017) and have lower decision-making autonomy than older mothers (Kamiya et al, 2018). Importantly, the adverse effects of these disadvantages on child nutritional status would be greater when children are younger.…”
Section: Discussionmentioning
confidence: 99%
“…In Niger, one-fourth of girls are married by age 15 years and three-fourths by age 18 years [ 1 ]. Studies have shown that child marriage can lead to negative sexual and reproductive health (SRH) outcomes for girls [ 2 , 3 ]. Marriage being a central expectation of Nigerien life [ 4 , 5 ], entering into a union helps both men and women fulfill their roles and thus, this practice has endured.…”
Section: Introductionmentioning
confidence: 99%
“…(Setiawati, 2018) Menunda usia pernikahan juga dapat meningkatkan pemberdayaan kesehatan wanita, dimana dengan begitu maka kesehatan anak pun akan turut meningkat dikarenakan berkurangnya kehamilan diusia dini. (Delprato & Akyeampong, 2017 Amin, S., Saha, J., & Ahmed, J. 2018.…”
Section: Efektivitas Intervensiunclassified